SOME CONSIDERATIONS ON THE CAUSES, TYPES, SYMPTOMS, AND METHODS OF BLOOD STOPPING BLOOD (Journal of Universal Science Research, 2023)
This article discusses the causes, types, symptoms and methods of stopping bleeding. It contains information about the main causes of bleeding, factors, and related processes in organs.